Age-related changes in the temporal processing of acoustical signals in the auditory cortex of rats - Bureš, Zbyněk; Pysanenko, Kateryna; Syka, Josef (Hearing research, 2021)
Age-related hearing loss is manifested primarily by a decreased sensitivity to faint sounds, that is, by elevation of the hearing thresholds. Nevertheless, aging also affects the ability of the auditory system to process temporal parameters of the sound stimulus. To explore the precision and reliability of auditory temporal processing during aging, responses to several types of sound stimuli were recorded from neurons of the auditory cortex (AC) of young and aged anaesthetized Fischer 344 rats. In response to broad-band noise bursts, the aged rats exhibited larger response magnitudes, a higher proportion of monotonic units, and also a larger variability of response magnitudes, suggesting a lower stability of the rate code. Of primary interest were the responses to temporally structured stimuli (amplitude-modulated (AM) noise, frequency-modulated (FM) tones, and click trains) recorded separately in the right and left AC. Significant differences of temporal processing were already found between the neuronal responses in the left and right AC in the young animals: for the click trains, the left hemisphere exhibited a greater responsiveness to higher repetition rates, lower vector strength values, and a lower similarity of responses. The two hemispheres were also affected differently by aging. In the right hemisphere, neurons in the aged animals displayed worse synchronization with the AM noise and clicks, but better synchronization with the FM tone. In the left hemisphere, neuronal synchronization with the stimulus modulation improved at a higher age for all three stimuli. The results show that the ability of the aging auditory system to process temporal parameters of the stimulus strongly depends on the stimulus type and on laterality. Furthermore, the commonly reported age-related decline in the temporal processing ability cannot be regarded as general as, at least at the neuronal level in the AC, objective measures of the temporal representation often exhibit age-related improvement instead of deterioration.
Keywords: Acoustic Stimulation; potkani inbrední F344; zvířata; Rats; reprodukovatelnost výsledků; Time Perception; Auditory system; Aging; akustická stimulace; vnímání času; Rats, Inbred F344; Auditory Cortex; Temporal processing; krysa rodu Rattus; Animals; Reproducibility of Results; sluchové korové centrum; Synchronization; Rate code